INNOVATIVE URBAN DEVELOPMENT: THE CONCEPT OF "SMART CITY" AND ITS IMPLEMENTATION IN THE U.S. (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Along with the rapid development of information and communication technologies in the 21st century, implementation of innovative urban development practices and approaches has become a pivotal trend and direction of contemporary urbanization process. Smart cities are considered to be the main practical outcomes of innovative urban development. Meanwhile, the concepts of "smart city" and sustainability are mutually connected and determined: thus, the concept of "smart sustainable city" has emerged to characterize the use of smart and innovative urban technologies for achieving long-term and balanced urban development in socio-economic, institutional, cultural, and environmental aspects. Innovative urban development gets a particular significance for the U.S., taking into account the great share of country's urban population (above 80%), distribution of large and densely-settled urbanized areas across the country, as well as the uniqueness of the factor of urbanization in American lifestyle, economy, and social relations. The theoretical section of this paper is devoted to the study of aforementioned theoretical ideas and peculiarities of innovative urban development smart sustainable cities. It is followed by a practical section, where relevant cases of 5 American smart cities (New York City, San Francisco, Columbus, Austin and Chicago) were studied, compared and summarized.
Keywords: innovative urban development; smart cities; U.S.; urban innovation system; smart sustainable cities